Dogface Soldiers. The Infantry Riflemen of the Army of the United States, and the war against Hitlers Wehrmacht in the Mediterranean and Northwestern Europe. - Büchl, Marco (Böhlau, 2016)
Dogface Soldiers is an interdisciplinary and image centered cultural history of the Army of the United States' infantry riflemen in the Mediterranean- and European Theaters of Operations of World War II. Its methods transcend the boundaries of conventional historiography and make use of Clifford Geertz's anthropological method of thick description as well as military used comprehensive analysis methods.